Apology as evidence of liability in medical disputes: a comparative study between the Shari'ah and civil law - Saleh, Muhammad Ridhwan; Jahn Kassim, Puteri Nemie; Ramlee Saad, Zulfakar (USIM Press, Universiti Sains Islam Malaysia, 2018)
Although seen as an effective tool in resolving medical disputes at an early stage, apology has yet to be fully embraced by medical practitioners in healthcare settings. This is due to the fact that the act of apologising has constantly been associated with admission of fault as well as confession of guilt. In addition, the components of apology which include expressions of guilt, remorse or self-criticism tend to have adverse evidentiary implications in potential lawsuits. Lawyers as well as insurance companies have also labelled the ‘act of apologising’ as suicide, due to the negative implications the act has on legal suits and medical indemnity coverages. In preserving the benefits of apologizing, several jurisdictions have introduced laws halting apologies from being put into evidentiary use by the courts of law. The act of apologising is also regarded as commendable under the Shari’ah as Allah swt has promised reward for those who forgive in many provisions of the Holy Qur’an. Showing patience and giving forgiveness is considered to be the best conduct for a good Muslim as Allah swt stated to the effect in Surah Al- Maidah, verse 13, that “… forgive them, and overlook (their misdeeds), for Allah loves those who are kind”. By employing qualitative methods of research, this paper aims to discuss the evidentiary implications of apology on court litigation under both the Shari’ah and Civil Law and whether the enactment of ‘apology laws’ will eventually encourage medical practitioners to embrace this benevolent act fully and globally.